Incentivos Tributarios y la Recaudación del Impuesto Predial de la Municipalidad Provincial de Barranca, 2022 - Dueñez Dionicio, Carol De La Paz (2023)
In the Provincial Municipality of Barranca, it is perceived that they fail to comply with their obligations (payment of salaries and wages of workers), and this is due to the fact that they do not apply effective tax incentives that allow increasing tax collection, and being able to finance themselves with their directly collected income. , to provide a scientific response to the perceived problem, we pose the following problem: How are tax incentives related to the collection of the property tax of the provincial municipality of Barranca, 2022? Likewise, we pose the following objective: Describe whether The tax incentives are related to the collection of the property tax of the provincial municipality of Barranca, 2022; The hypothesis proposed is: Tax incentives are related to the collection of property tax of the provincial municipality of Barranca, 2022, the research is basic, at a Descriptive - Correlational level, with a non-experimental design, cross-sectional, since it does not The variables were manipulated, the technique used is the survey and as an instrument the questionnaire was applied to a sample of 64 residents of the Barranca district, the data were processed and analyzed in the statistical program SPSS version 23, obtaining as a result that the association between tax incentives and property tax collection of the provincial municipality of Barranca, 2022; It is positive at an optimal level directly proportional, according to the significance of 0.001 and Spearman's Rho of 0.980, this means that when tax incentives are increased at the same time, property tax collection increases, which benefits society.